Holmes Tremor due to Artery of Percheron Infarct: Clinical Case and Treatment Using Deep Brain Stimulation of the Vim and ZI Targets. (7th January 2020) - O'Shea, Sarah A.; Elkind, Mitchell; Pullman, Seth L.; Ford, Blair
Background: Holmes tremor (HT) arises from disruption of the cerebellothalamocortical pathways. A lesion can interrupt the projection at any point, resulting in this tremor. We describe a case of HT due to the rare artery of Percheron infarct and its successful treatment using deep brain stimulation. Case report: A 62-year-old woman with a right medial cerebral peduncle and bilateral thalamic stroke developed HT. Ventral intermediate nucleus (Vim) zona incerta (ZI) deep brain stimulation (DBS) surgery was performed, with improvement in her tremor. Discussion: Our case supports the theory that the more caudal ZI target in combination with Vim is beneficial in treating poorly DBS-responsive tremors such as HT.